Promoter Methylation Analysis of IDH Genes in Human Gliomas - Flanagan, Simon; Lee, Maggie; Li, Cheryl C.; Suter, Catherine M.; Buckland, Michael E. (Frontiers in Oncology, 2012)
Mutations in isocitrate dehydrogenase (IDH) -1 or -2 are found in the majority of WHO grade II and III astrocytomas and oligodendrogliomas, and secondary glioblastomas. Almost all described mutations are heterozygous missense mutations affecting a conserved arginine residue in the substrate binding site of IDH1 (R132) or IDH2 (R172). But the exact mechanism of IDH mutations in neoplasia is not understood. It has been proposed that IDH mutations impart a ‘toxic gain of function’ to the mutant protein, however a dominant-negative effect of mutant IDH has also been described, implying that IDH may function as a tumour suppressor gene. As most, if not all, tumour suppressor genes are inactivated by epigenetic silencing, in a wide variety of tumours, we asked if IDH1 or IDH2 carry the epigenetic signature of a tumour suppressor by assessing cytosine methylation at their promoters. Methylation was quantified in 68 human brain tumours, including both IDH-mutant and IDH wildtype, by bisulfite pyrosequencing. In all tumours examined, CpG methylation levels were less than 8%. Our data demonstrate that inactivation of IDH function through promoter hypermethylation is not common in human gliomas and other brain tumours. These findings do not support a tumour suppressor role for IDH genes in human gliomas.